A loose sculpture of Lord Brahma - Temples of India Project Team (Jio Institute, 2024)
A loose sculpture of Brahma is found lying next to the pratoli (entrance gateway), in the premises of the Mahanaleshwar temple complex. The three-faced, four-handed, seated figure of Brahma is shown holding a pustaka (book) in the upper left hand and a kamandalu (sacrificial pot) in the lower left while the attributes in the right hand are lost. The bearded pot-bellied figure with jatamukuta (crown of mattered hair) is placed inside a niche.